2021
DOI: 10.1111/cei.13575
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes: innate immune cells in atopic dermatitis

Abstract: Summary The skin is a unique immune organ that constitutes a complex network of physical, chemical and microbiological barriers against external insults. Keratinocytes are the most abundant cell type in the epidermis. These cells form the physical skin barrier and represent the first line of the host defense system by sensing pathogens via innate immune receptors, initiating anti‐microbial responses and producing various cytokines, chemokines and anti‐microbial peptides, which are important events in immunity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 104 publications
1
68
0
Order By: Relevance
“…We also found that triggered pyroptotic cell death of keratinocytes was suppressed by mdivi‐1, Keratinocyte pyroptosis might affect AD in two aspects including barrier disruption, and the release of the pro‐inflammatory cytokines IL‐1β and IL‐18 aggravating the development of AD. IL‐1β and IL‐18 promote the chemotaxis of inflammatory cells and regulate TH2 cytokine production and histamine 25,26 . Our in vitro results at least demonstrated the suppressive role of mdivi‐1 in the activation NLRP3 inflammasomes and pyroptosis in the keratinocytes under AD‐like conditions.…”
Section: Discussionmentioning
confidence: 55%
“…We also found that triggered pyroptotic cell death of keratinocytes was suppressed by mdivi‐1, Keratinocyte pyroptosis might affect AD in two aspects including barrier disruption, and the release of the pro‐inflammatory cytokines IL‐1β and IL‐18 aggravating the development of AD. IL‐1β and IL‐18 promote the chemotaxis of inflammatory cells and regulate TH2 cytokine production and histamine 25,26 . Our in vitro results at least demonstrated the suppressive role of mdivi‐1 in the activation NLRP3 inflammasomes and pyroptosis in the keratinocytes under AD‐like conditions.…”
Section: Discussionmentioning
confidence: 55%
“…In the keratinocytes of AD patients, the expression and secretion of cytokines IL-25, IL-33, and TSLP, and the chemokines TARC, MDC, and RANTES, which are directly or indirectly related to the activation of Th2 cells, are increased [ 64 ]. In addition, expression of CCR4, a receptor for TARC and MDC, increases on the surface of Th2 cells, thereby increasing Th2 cell invasion and activity [ 29 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes such as HaCaT cells play central roles in skin disease, the initiation and maintenance of AD (Chieosilapatham et al 2021 ). Therefore, HaCaT cells are commonly used for the in vitro testing of anti-inflammatory and anti-atopic skin agents (Colombo et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%